"Decrypting Dangers: Exploring the Nexus Between Cryptocurrency and Financial Crime" (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The rise of Bitcoin and other cryptocurrencies has brought about a new era of financial transactions, promising unparalleled anonymity and decentralization. However, it also poses significant risks as it can facilitate financial crimes such as fraud, cyber theft, and money laundering. This research paper aims to examine the complex relationship between cryptocurrencies and illicit activities and thoroughly analyze the mechanisms that enable such crimes. Moreover, it seeks to identify the challenges these illicit activities pose to regulators worldwide and offer practical strategies for mitigating risks while harnessing the potential benefits of digital currencies.